Attitude of Community and village leaders towards the Community –Based Programme in The Faculty of Medicine – University of Gezira, Sudan - Abdalla, M.E.; Mirghani, O.A.; Hakim, Y. (مجلة الجزيرة للعلوم الصحية; مجلد 4 عدد 1 (2008), 2008)
Objective: The objective is to describe the attitude of the community and village leaders towards the community based programme implemented in the Faculty of Medicine – University of Gezira(FMUG). Introduction: The curriculum is unique, with 30% of it is community-Based. So the attitude of the community is highly considered in the evaluation of the  programme. Methods: Twenty-four community leaders from the 48 members of the State Assembly were interviewed. Forty-eight of the village leaders from nine villages in El managil area where the three phases of the Interdisciplinary Field Training, Research and Rural Development Programme IFTRRDP have been completed recently were also interviewed through a pre structured interview by independent, trained personnel and their responses were collected and analyzed. Results: All the community and village leaders knew most of the objectives of the school. The expectations of the community from the school are the health education and treatment of patient. Community benefits from the presence of the students were rated as good and excellent by 58% of the community leaders and 87.8% of the village leaders. More visits for strengthening the relation between the school and the community was suggested by 72.9% (n=35). 18.8% (n=9) of the village leaders participated in the evaluation of students. Discussion: Objectives of the community based programme at  FMUG are very well known and accepted by the community. This support the FMUG community partnership and services  beside training  students . The expectations of the community are fitting fully with the objectives of the school. Conclusion: The attitude of the community towards the community based programmes in FMUG is positive ,this can be sustained by ensuring more involvement of them in all steps of the programme. More studies to describe and measure the attitudes of the community in other CBE medical schools is recommended for comparison.  OBJECTIVE: The objective of this work is to describe the attitude of the community and village leaders towards the community-oriented programme implemented in the Faculty of Medicine – University of Gezira, Sudan as a part of the second comprehensive evaluation of the school's programme.